Practical and Efficient Synthesis of Hydroxyaryl Ketones Catalyzed by HF@SiO2 under Solvent-free Condition - Paghandeh, Hossein; Saeidian, Hamid; Ghaffarzadeh, Mohammad (Letters in Organic Chemistry, 2018)
A wide variety of hydroxyaryl ketones bearing different motifs was successfully synthesized with good yields and excellent selectivities in the presence of HF@SiO2 as an environmental friendly acid under solvent-free condition. Mild and green reaction conditions and excellent yields (50-91%) make this method an attractive method for the efficient synthesis of hydroxyaryl ketones. Fries rearrangement of phenyl benzoate in the presence of HF@SiO2 led to p-hydroxybenzophenone, while phenyl acetate in the same conditions produced o-hydroxyacetophenone as a single isomer.
Keywords: isomer